De vasco-affaire, een drama in de woningbouw in de oostelijke mijnstreek - Laugs, John (Studies over de sociaaleconomische geschiedenis van Limburg, 2020)
In the postwar era the Netherlands were confronted with a dramatic housing shortage aggravated by a lasting high birthrate. Local government in particular faced the herculean task of having to build rapidly and in large quantities. The prefab method invented by the Verenigde Aluminium en Staalconstructiemaatschappij N.V (Vasco) seemed to offer an easy solution. The municipalities of Kerkrade and Heerlen in the south of Limburg were eager to offer contracts to the building company. Despite the rosy prospects, however, the association with Vasco ended in bitter disappointment. The article explores the painstaking process from the first contacts between the building company and the municipalities in the late 1950s, to the eventual settlement in 1979.